Ekstrapolasi Keterampilan Ilmiah Melalui Penerapan Pembelajaran Projek Berbasis Presentasi Pada Calon Guru Pendidikan Ilmu Pengetahuan Alam Di Masa Pandemic Covid-19 - Muh. Tawil; Muhammad Aqil Rusli; Hasanuddin Bakara (SEMINAR NASIONAL DIES NATALIS 62, 2023)
The purpose of this research is to explore the scientific attitudes and scientific skills of Natural Sciences teacher candidates by implementing presentation-based project learning. The number of research samples was 98 prospective teachers for the 2022/2023 academic year in the Science Education Study Program at the Faculty of Mathematics and Natural Sciences, Makassar State University. The research method applied is quasi-pre-experimental method. The results of the descriptive statistical analysis found that: 1) 100 percent of science teacher candidates were active in participating in presentation-based project learning during the Covid-19 pandemic; 2) the responses of prospective science teachers to the implementation of project-based learning were very positive, 3) the average score of scientific attitudes was 49.49 which was included in the high category, 4) the average score of scientific skills was 91.54 which was included in the high category. The conclusion of presentation-based project learning can develop the scientific attitude of science teacher candidates. Recommendations: 1) presentation-based project learning can be applied in developing scientific attitudes and scientific skills, 2) presentation-based project learning can activate practicum activities during (online) during the Covid-19 pandemic.